2016
DOI: 10.1117/1.jbo.21.5.050902
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography for embryonic imaging: a review

Abstract: Embryogenesis is a highly complex and dynamic process, and its visualization is crucial for understanding basic physiological processes during development and for identifying and assessing possible defects, malformations, and diseases. While traditional imaging modalities, such as ultrasound biomicroscopy, micro-magnetic resonance imaging, and micro-computed tomography, have long been adapted for embryonic imaging, these techniques generally have limitations in their speed, spatial resolution, and contrast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 176 publications
(177 reference statements)
0
56
0
Order By: Relevance
“…This unique spatial imaging scale of OCT has enabled applications ranging from biomedical research [25][26][27] to clinical diagnosis and monitoring [28][29][30]. Embryology is a major research area where OCT shows great promise as a high-resolution unlabeled imaging tool [31][32][33]. With the primary focus on the cardiovascular development and abnormalities, OCT has been reported able to reveal detailed structures of the embryonic heart comparable to histology [34][35][36], to capture four-dimensional dynamic cardiac activities [37][38][39], to quantify biomechanics of the heart tube [40][41][42], to assess cardiac hemodynamics [43][44][45], to characterize novel mutant heart phenotypes [46][47][48], and to investigate cardiac responses to physical and chemical manipulations [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…This unique spatial imaging scale of OCT has enabled applications ranging from biomedical research [25][26][27] to clinical diagnosis and monitoring [28][29][30]. Embryology is a major research area where OCT shows great promise as a high-resolution unlabeled imaging tool [31][32][33]. With the primary focus on the cardiovascular development and abnormalities, OCT has been reported able to reveal detailed structures of the embryonic heart comparable to histology [34][35][36], to capture four-dimensional dynamic cardiac activities [37][38][39], to quantify biomechanics of the heart tube [40][41][42], to assess cardiac hemodynamics [43][44][45], to characterize novel mutant heart phenotypes [46][47][48], and to investigate cardiac responses to physical and chemical manipulations [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic development is a highly complex and dynamic process and its visualization is crucial for fully comprehending the complex phenotypic processes [1,2], which are essential for studying the development and gene regulation of insect embryos.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Stephen Boppart's group first applied OCE to a tissue-engineered construct and to a developmental biology model -the xenopus laevis [23] (xenopus laevis has now largely been supplanted by the zebrafish and mice in developmental biology -a recent review of this field can be found in [24]). The basic method, compression, time-domain OCT and speckle tracking to determine cross-sectional displacement, had not changed since Schmitt's initial demonstration.…”
Section: Optical Coherence Elastography Prehistorymentioning
confidence: 99%